Peran kelompok tani, pendapatan dan pendidikan terhadap tingkat kesejahteraan petani padi: Studi pada Petani Kalibening Salatiga - Maulana, Gunawan Figar; Rofiuddin, Mohammad (Nur Science Institute, 2023)
The purpose of the researchers to analyze how the influence of group roles, income and education on the level of welfare of farmers using the perspective of Ibn Khaldun's theory. The population in this study is the Muslim community of Kalibening Village. The sampling technique used was purposive sampling with a total of 90 people. The results of this study indicate that the role of the group has a significant positive effect on the Welfare level of Farmers. Income has a significant positive effect on the level of Farmer Welfare. Education has a significant positive effect on the level of Farmer Welfare.